Perspektif Pendidikan Kristen dalam Menghadapi Quarter-Life Crisis pada Usia Dewasa Awal - Gian Gideon Akin (Voice, 2023)
A quarter-life crisis is a phase where a person feels anxious about their life in the future. The transition from adolescence to adulthood has several challenges that are certainly different from the previous developmental process. As a person progresses towards a more mature age, they will face new challenges such as work, marital status, and mindset changes. This phase often causes stress for some people. Therefore, an alternative solution is needed to shape the mindset so that people in young adulthood can face it with the right mindset. The researcher will use a psycho-social approach to identify this problem and provide a perspective from Christian education. The article with the title Perspective of Christian Education in Dealing with Quarter-Life Crisis in Early Adulthood uses descriptive qualitative methods with references from several studies that have been conducted in the last five years. The results of this study report that the Christian perspective is expected to be a solution in dealing with quarter-life crises so that every adult can realize that the emotional crisis they feel can be overcome by themselves because they are the ones who decide to choose the direction of their life plans.